Numerical analysis of deformation and flow in the proximal area of the urethra - Rudyk, Rafał; Malinowski, Marek; Mackiewicz, Agnieszka; Będziński, Romuald; Noszczyk-Nowak, Agnieszka; Skonieczna, Joanna; Madej, Jan (Zielona Góra: Uniwersytet Zielonogórski)
Pathological conditions of a male urethra, including fibrosis, have a mechanical background along the entire length of the urethra. They may be caused by excessive deformation of the urethra locally or globally. The condition of prolonged overload causes abnormal tissue remodelling and, consequently, the formation of a thick layer of scar tissue differentiated from the connective tissue of the urethra.
Keywords: urethra; stress-strain characteristic; FEM; CFD; urinary flow